MAIN DIRECTIONS FOR IMPROVING AGROFRANCHING IN THE AKMOLIN REGION - Omarkhanova, Zh.M.; Tleuzhanova, D.A.; Amangeldijeva, Zh. A.; Baymagambetova, Z.A. (Academic Journal of Physical and Chemical Sciences, 2018)
The main difference between an agro franchise and a simple farm is that the franchisee does not care about the sale of the products produced, the agro franchiser undertakes these concerns. In the Akmola region in its development has an actively dominant agrarian context, the formation of innovative agro-clusters today is an urgent and necessary task for the national economy. The purpose of such entities is to assist in the formation of an innovative environment in the agrarian sector, within the framework of this research topic, this is agrofranchising. To ensure the success of entrepreneurs and taking into account the possible lack of knowledge, potential franchisees should be assisted in drawing up real business plans, and subsequently accounting reports, legal and personnel support, again from the state.